The national revalidation and electronic configuration of the La Crosse Wellness Inventory - Squire, Kathleen (My University, 2000)
Content validity of the 182-item La Crosse Wellness Inventory (LWI) was determined by review of literature and review by jury of experts. The national jury sample consisted of 25 selected experts aligned with one or more of the 9 areas of the LWI. Jury members were asked to rate the acceptability level of each statement on a 5-point Li~ert-types cale regarding its ability to assess a person's level of wellness within the context of a particular wellness area. Additionally, jury members were encouraged to comment on any and all statements. Following jurification, 80 statements were revised, 6 statements were eliminated, and 1 statement was added. The revised LWI was comprised of 178 items. The LWI software was constructed utilizing Internet and web-based technology. HyperText Markup Language (HTML) was adapted to construct the web pages, and Java programming language was used to make the software interactive. The LWI software components included static web pages, the client-side applet, and the server-side application To complete the La Crosse Wellness Project, users are asked to enter their data into the Wellness Development Process in order to develop a personalized wellness plan
Keywords: Health promotion; La Crosse Wellness Inventory (University of Wisconsin--La Crosse) - Software; La Crosse Wellness Inventory (University of Wisconsin--La Crosse) - Validity